2018
DOI: 10.4236/sgre.2018.93004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T-Coefficients Using the Columnar Cylindrical Orientation of Solar Cell Grain

Abstract: We report the study of the temperature dependance of the performance electronic parameters of an N-P solar cell by considering as model, the columnar cylindrical orientation associated to the dynamic junction velocity (SF) concept. We presented the photocurrent-photovoltage (I-V) and Power-photovoltage (P-V) characteristic curves. The short-circuit photocurrent (I sc ), the open circuit photovoltage (U oc ), the fill factor (FF) and the efficiency (η) are linearly dependent on the temperature. The temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This result is in agreement with increase of photocurrent density and the significant decrease of photovoltage with temperature increase. This result is in agreement with those of Leye et al [15], Chander et al [16] and Agroui et al [17].…”
Section: Effect Of Temperature On Electric Powersupporting
confidence: 94%
“…This result is in agreement with increase of photocurrent density and the significant decrease of photovoltage with temperature increase. This result is in agreement with those of Leye et al [15], Chander et al [16] and Agroui et al [17].…”
Section: Effect Of Temperature On Electric Powersupporting
confidence: 94%
“…There are thus several configurations: we encounter parallelepiped or cubic configuration with the classic horizontal junction between the base and emitter assuming that the generated carriers move from the base to the emitter parallel to the illumination [2] [3] [4] and vertical junction for the purpose to reduce the path of the carriers to the junction to decrease recombination in the base of the cell [5] [6] [7]. Also, we can find in the literature cylindrical configurations with planar [8] [9] [10] and radial [11] [12] [13] [14] p-n junction as depicted in Figure 1 which is deeply investigated in this paper. Trabelsi et al [9] and Mbodji et al [8] carried out work on a cylindrical grain N + /P polycrystalline solar cell.…”
Section: Introductionmentioning
confidence: 99%
“…Leye et al [10] studied the temperature effect on the performance of an N/P solar cell considering the columnar cylindrical grain. They showed that when the temperature increases the short circuit increases however, the open circuit decreases.…”
Section: Introductionmentioning
confidence: 99%